Retroviral Capsid Core Stability Assay - Renner, Tyler Milston (Bio Protoc, 2018)
Structural stability of the capsid core is a critical parameter for the productive infection of a cell by a retrovirus. Compromised stability can lead to premature core disassembly, exposure of replication intermediates to cytosolic nucleic acid sensors that can trigger innate antiviral responses, and failure to integrate the proviral genome into the host DNA. Thus, core stability is a critical feature of viral replicative fitness. While there are several well-described techniques to assess viral capsid core stability, most are generally time and labor intensive. Recently, our group compared the relative stability of murine leukemia virus capsid cores using an in vitro detergent-based approach combined with ultracentrifugation against the popular fate of capsid assay. We found that both methods reached similar conclusions, albeit the first method was a significantly simpler and faster way to assess relative capsid core stability when comparing viral mutants exhibiting differences in core stability.